THE IMPLEMENTATION OF GAME IN TEACHING ENGLISH VOCABULARY - Syarfuni (Jurnal Visipena, 2010)
The primary activities of students in the classroom is learning. Successful learning is only the right way to lead the process. Good learning atmosphere method and technique will guide the students to learn more serious and meaningful. To accomplish such condition, the teacher must create some types and attractive method or technique in the classroom. To avoid the students bore in the classroom the teacher should use some types of game to be an alternative solution to handle the problem. Games as a matter of fact can help and encourage students to sustain their interest in learning English. In this paper the writer wants to share experiences about the implementation of game in teaching English.